Revision of the genus Ultragryllacris (Orthoptera: Stenopelmatidae: Gryllacridinae), with description of new species - Dawwrueng, Pattarawich; Gorochov, Andrei V.; Suwannapoom, Chatmongkon (Zootaxa, 2023)
The genus Ultragryllacris was revised. All its species and subspecies, including U. jiaranaisakuli sp. nov., U. chandra sp. nov. from Western Thailand and U. intermediata sp. nov. from Northern Thailand are here described and redescribed. They are known from Thailand and China. The new species differs from all the other representatives of this genus mainly in different body coloration, shape of projection of male 9th abdominal tergite and sclerotized area of female subgenital plate. The following taxonomical changes are also proposed: U. pulchra alboclypeata Gorochov et Dawwrueng, 2015, U. p. nan Ingrisch, 2018 and U. p. rubricapitis Bin et Bian, 2021 are raised to species status (U. alboclypeata stat. nov., U. nan stat. nov. and U. rubricapitis stat. nov.) due to some characteristic structures in both male and female; U. triangula Ingrisch, 2018 is downgraded to subspecies of U. alboclypeata (U. a. triangula stat. nov.). Previously unknown male of U. a. alboclypeata and female of U. nan are described. A key to all known species is given.